A Study on Outcomes of Surgical Treatment of Depressed Skull Fractures - Muhammad Idris Khan, Adnan Munir (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Trauma is a significant issue in both industrialized and developing nations. A significant risk factor for death in the young population is head injury Objective: To assess the outcomes of surgical treatment of depressed skull fractures Methodology: The current study was prospective study was done at Neurosurgery department of Khyber teaching Hospital Peshawar. The study duration was one years from March 2022 to March 2023. Causes of the depressed skull fracture, time since the injury, the kind of fracture, the location of the fracture, the reason for the fracture, the clinical state, and the CT scan results were noted. All patients had CT scans. DSF greater than 5 mm, disfiguring cosmetic fractures, and sinus fractures were surgically treated. The whole set of data was examined using SPSS 23.00. Results: In our study, totally 80 patients were enrolled. The male patients in our study were 58 (72.5%) whereas female patients were 22 (27.5%). In the outcomes based on GCS, completely recovered patients were 58 (72.5%) patients, 11 (13.75%) were moderately disabled, 8(10%) severely disabled whereas 2(2.5%) patients were demised. Conclusion: Trauma from depressed fractures is common in neurosurgical wards. One of the most important variables influencing outcome prediction is the neurologic state as indicated by the Glasgow coma scale. About two-thirds of patients who undergo surgical therapy of depressed skull fractures get successful results while one- third of patients are still classified as having severe disabilities. Complications, including death, are common after a depressed skull fracture. Keywords: Outcome; surgical treatment: depressed skull fractures